2019
DOI: 10.26418/ijli.v1i1.33401
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Gender Bias in When English Rings A Bell Textbooks

Abstract: This thesis reports on the gender bias contained in English e-textbook for junior high school students provided by the ministry of education. The study used a framework proposed by Porreca (1984) as guidance. The framework is distinctive because it examines the problem of gender representation contained in textbook. Based on the framework the study focused on gender visibility in text and illustration, gender firstness, occupational role, gender neutral nouns and gender specific nouns, masculine generic constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…shows a new perspective that they could also be seen as subservient instead of always dominant (Dabbagh, 2016;Julianti et al, 2019;Suhartono & Kristina, 2018).…”
Section: B Women's Domination In Conversationmentioning
confidence: 99%
See 3 more Smart Citations
“…shows a new perspective that they could also be seen as subservient instead of always dominant (Dabbagh, 2016;Julianti et al, 2019;Suhartono & Kristina, 2018).…”
Section: B Women's Domination In Conversationmentioning
confidence: 99%
“…In Indonesia, Ariyanto (2018) revealed gender bias portrayal in the English textbook for junior high school. Julianti et al (2019) also found that the book included traditional construction of proper space for men and women. Female characters were mostly depicted in domestic spheres, while the male characters were mostly outdoors.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Dalam lingkup pendidikan, bias gender sering dijumpai pada materi yang dimanifestasikan melalui buku teks pelajaran (Julianti, L., & Ikhsanudin, I., 2019, Selvi, A. F., & Kocaman, C., 2021. Bias gender dalam buku teks pelajaran terdapat dalam makna suatu teks maupun gambar yang dimuat di dalamnya (Ferree, M. M., & Hall, E. J., 1990, Elmiana, D. S., 2019.…”
Section: Tinjauan Pustakaunclassified